IDENTIFIKASI BAHAYA, PENILAIAN RESIKO, DAN PENGENDALIAN RESIKO PADA AKTIVITAS TAMBANG BATUBARA DI PT. KIM KABUPATEN MUARO BUNGO, PROVINSI JAMBI - Miftahul Jannah; Rijal Abdullah; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2015)
Based on the data obtained from the company, the data accidents that occurred between the years 2012-2014 there were 222 cases of accidents, as well as activities that are harmful to workers at risk of injury, lost work days, and the cost of repair tools. The causes of such unsafe acts and unsafe conditions of the workers. The purpose of this study were: 1) Revealing the dangers that occur in coal mining activities. 2) Uncover the risk of hazards that occur in the coal mining activities. 3) Disclose the value of the likelihood and severity of hazards that occur in the coal mining activities start from land clearing activities until the loading of coal in the stockpile.This type of research is descriptive with quantitative approach, in which data is collected or obtained from direct observation in the field and interviews with leaders and staff as well as employees of the company who are competent in connection with the object of research. The data is taken from the data mining activities, the risk of hazards that occur in the coal mining activities.Results of the study revealed that the risk of hazards that occur in the coal mining activities at PT. Kuansing core affluent who are at a high level going on the road hauling.